2014
DOI: 10.1111/camh.12059
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in Practice: Further evidence on the effectiveness of the strengths and difficulties added value score as an outcome measure for child and adolescent services

Abstract: Background: The Strengths and Difficulties Added Value Score (SDQ AVS) uses a large epidemiological study to predict follow-up parental SDQ scores for the evaluation of routine outcomes. Method: We tested the prediction of the SDQ AVS derived from a national population survey separately on scores for the waiting list control and intervention groups in a randomised controlled trial. If the SDQ AVS is to be clinically useful, it needs to function as expected across different populations. Results: In the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…When conducting evaluations of interventions, there are several factors that may cause the scores on follow‐up outcome measures to decrease, such as attenuation (i.e. the inclination for clients to report less on the second round of measurements), regression to the mean and perceived decrease in difficulties at follow‐up due to adolescents generally being referred to the service when their difficulties are most severe (Fugard et al., ; Rotheray et al., ). For these reasons, it is important to compare the results from an intervention study to a control sample in order to determine whether there is more or less improvement than would have been predicted without the FFT intervention.…”
Section: Introductionmentioning
confidence: 99%
“…When conducting evaluations of interventions, there are several factors that may cause the scores on follow‐up outcome measures to decrease, such as attenuation (i.e. the inclination for clients to report less on the second round of measurements), regression to the mean and perceived decrease in difficulties at follow‐up due to adolescents generally being referred to the service when their difficulties are most severe (Fugard et al., ; Rotheray et al., ). For these reasons, it is important to compare the results from an intervention study to a control sample in order to determine whether there is more or less improvement than would have been predicted without the FFT intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies, as described above (Ford et al, 2009;Rotheray et al, 2014) have demonstrated that DS greatly inflate the estimates of change while the SDQ AVS does adjust for attenuation, random fluctuation and regression to the mean as expected. The SDQ AVS, therefore, does seem to be the most rigorous way to assess change in our study.…”
Section: Discussionmentioning
confidence: 67%
“…It seems unlikely, however, that our choice of measures completely explains our failure to detect improvement as others using these measures have been able to do so. The mean SDQ AVS for clinics sending data to CORC have been positive (mean=0.19 see www.CORC.uk.net, Wolpert et al, 2012b;Fugard et al, 2014), and reanalysis of trial data suggests that the SDQ AVS functions as expected (Ford et al, 2009;Rotheray et al 2014). Similarly, the smaller study based on one of the services that participated in the current work (Byrne et al 1999), Australian clinics working secondary school-age children (Matthai et al, 2003) and routine data from an Inner London clinic on parenting (Hurst et al, 2014) detected clinically and statistically significant change over a similar time period using the SDQ.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Another advantage -currently available only for the parent version -is that an "added-value score" (AVS) can be calculated using someone's initial scores and scores six months later. (Ford, Hutchings, Bywater, Goodman, & Goodman, 2009;Rotheray S et al, 2014) The AVS allows the impact of treatment to be estimated above and beyond spontaneous improvement and factors like regression to the mean. So far there have been two tests of the score's predictions using data from randomised controlled trials (RCTs) of parent training.…”
Section: Children and Young People's Iaptmentioning
confidence: 99%